2018
DOI: 10.1088/1475-7516/2018/11/021
|View full text |Cite
|
Sign up to set email alerts
|

Natural Inflation with a periodic non-minimal coupling

Abstract: Natural inflation is an attractive model for primordial inflation, since the potential for the inflaton is of the pseudo Nambu-Goldstone form, V (φ) = Λ 4 [1 + cos(φ/f )], and so is protected against radiative corrections. Successful inflation can be achieved if f > ∼ few MP and Λ ∼ mGUT where Λ can be seen as the strong coupling scale of a given non-abelian gauge group. However, the latest observational constraints put natural inflation in some tension with data. We show here that a non-minimal coupling to gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 29 publications
2
43
0
Order By: Relevance
“…introducing a new periodic non-minimal coupling to gravity [25]. The authors in [25] showed that the new model leads to a better fit with observation data thanks to the introduction of a new parameter in the nonminimal coupling term, with n s and r values well within 95% C.L.…”
Section: This Work Concerns a Recently Proposed Extension Of The Orig...mentioning
confidence: 99%
See 2 more Smart Citations
“…introducing a new periodic non-minimal coupling to gravity [25]. The authors in [25] showed that the new model leads to a better fit with observation data thanks to the introduction of a new parameter in the nonminimal coupling term, with n s and r values well within 95% C.L.…”
Section: This Work Concerns a Recently Proposed Extension Of The Orig...mentioning
confidence: 99%
“…In the context of the present problem and the effective theory treatment, we restrict ourselves to the condition k ≪ 10 −6 M p so that k 0 k 2 m 2 ≪ 1 (more on this later) using the order-ofmagnitude estimates of parameters in Eq. ( 6) from the results of [25]. Hence, logs involving this fraction can be expanded in a Taylor series.…”
Section: Renormalization and Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as pointed out in the introduction, such term largely breaks Weyl symmetry. 14 See, however, Ref [71]. for a discussion of non-minimal couplings in natural inflation.…”
mentioning
confidence: 99%
“…Recently, an extension of the original natural inflation model was proposed that introduces a new periodic nonminimal coupling to gravity [3]. This modification leads to a better fit with observation data, with n s and r values well within 95% C.L.…”
Section: Introductionmentioning
confidence: 99%